Investment Scheme in Islamic Insurance Institutions - Fala Akbar Fathoni; Mochammad Hafidh Alifuddin; Rofiqotul Izza; Fatimah Sari Dewi; Lilik Rahmawati (STIS DAFA MATARAM, 2020)
Sharia investment is an activity that generates benefits from the results of fund management, where the results of these benefits are divided into profit sharing between the owner and fund manager. And investment can also be called an investment activity in several sectors (both the financial sector and the real sector) where in a certain period will produce the expected benefits. One form of sharia investment is investment in sharia insurance institutions. The purpose of this paper is to explain the sharia insurance investment scheme. The research method used in this paper is a qualitative research method that is the type of research that is artistic and interpretive, the results of the research are only interpreted into the data found in the field, how to get the data is done by interviewing to get information from a resource person of a member of the party PT. Family Takaful Insurance. Investment in Islamic insurance when investing participant funds is only placed in Islamic investment instruments that have been listed on the Indonesia Stock Exchange (IDX) under the supervision of the Indonesian Ulema Council (MUI). Islamic insurance investment in PT. Asuransi Takaful Keluarga is in the form of savings, and the savings product is divided into two namely traditional products such as Islamic deposits and non-traditional products such as Islamic stocks, sukuk, mutual funds.